REDESIGN SIGN SYSTEM PUSKESMAS LUBUK BUAYA KOTO TANGGAH KOTA PADANG - NANDA KURNIA PUTRA, Dr. M. Nasrul Kamal, M.Sn., Dra. Jurpiani, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The lack of information about facilities and space at the Lubuk Buaya Padang Health Center formed the visitors to be confused. Therefore, the existence of a sign system at the Lubuk Buaya Padang Health Center will make it easier for visitors to get information. The redesign of the Lubuk Buaya Padang health center sign system that is meaningful, communicative and simple is a good solution. This redesign of the gelatin sign system can be applied to the Lubuk Buaya Padang Health Center. The design method used is a Glass Box method, while the data is retrieval, interview and documentation. The completion of the analysis used is the 5W + 1H analysis model. The main media of this design are identification marks, while the supporting media consists of wayfindig, safety signs, traffic signs, infographics, table names, x-banners and patient cards.Keywords : Redesign Sign System, Lubuk Buaya Padang Health Center.